Influence of nutrient medium composition on the morphological characteristics of culture of dorsal root ganglion cells of neonatal piglets - AlіS.; SidorenkoО.; Bozhok, G. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2018)
Dorsal root ganglion (DRG) is a potential source of neural stem cells because it contains neural crest derived cells that are capable to differentiate into neurons and glial cells. Cell cultures obtained from animals that are close to humans by physiological characteristics can be regarded as an adequate modern model for in vitro studies. In this respect, DRG cell culture obtained from the domestic pig (Sus scrofa domesticus) is a convenient model. The aim of the work was to obtain a primary cell culture of DRG of neonatal piglets and to study its morphological and proliferative properties depending on culture medium composition. The composition of the media prepared on the basis of α-MEM varied depending on the presence of fetal calf serum (FCS) or its modern supplements B-27 and NeuroMax. It is established that morphological differences of primary DRG cell cultures of neonatal pigs depend on the composition of the nutrient medium. When cultured in the presence of 10% FCS, the formation of monolayer which includes satellite glial cells (SGC) and fibroblast-like cells was observed. Small colonies of neurons producing long processes were on the monolayer. When cultured in the presence of NeuroMax and B-27 supplements, the bulk of the cells is not attached, but organized into floating multicellular spheroids (MS). With the passage of culture obtained in the presence of 10% FCS, rapid attachment and proliferation of cells was observed. When MS obtained in the presence of NeuroMax and B-27 were transferred to the medium with 10% FCS, the attachment of MS to the substrate and cell migration were observed. The cells retain the ability to actively proliferate, because the monolayer achieves confluence by 5–7 days of subculture. Regardless of the composition of the primary culture medium, there were 3 morphologically different types of cells in the subcultures: SGC, neuron-like and fibroblast-like cells. The type of cells prevailing in the subculture depends on the composition of the nutrient medium. When MS is transferred from a B-27-containing medium, a significant growth of fibroblast-like cells is observed, whereas when MS is transferred from NeuroMax-containing medium MG and neuron-like cells were abundant.